Explorando diferentes mutações de um algoritmo genético para o Curriculum-Based Course Timetabling Problem - Manica, João Edison Roso (2024)
In this work, two mutations of a genetic algorithm for the Curriculum-Based Course Timetabling (CB-TT) problem are proposed, implemented, and validated. One of the mutations is based on a forward checking mechanism and the other on a repair mechanism. It is concluded that, compared to existing mutations, the number of conflicts in the main constraints was reduced.